2009
DOI: 10.1021/nn901221k
|View full text |Cite
|
Sign up to set email alerts
|

P25-Graphene Composite as a High Performance Photocatalyst

Abstract: Herein we obtained a chemically bonded TiO(2) (P25)-graphene nanocomposite photocatalyst with graphene oxide and P25, using a facile one-step hydrothermal method. During the hydrothermal reaction, both of the reduction of graphene oxide and loading of P25 were achieved. The as-prepared P25-graphene photocatalyst possessed great adsorptivity of dyes, extended light absorption range, and efficient charge separation properties simultaneously, which was rarely reported in other TiO(2)-carbon photocatalysts. Hence,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

113
2,021
3
9

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 3,018 publications
(2,200 citation statements)
references
References 25 publications
113
2,021
3
9
Order By: Relevance
“…Furthermore, the radius of the semicircle obtained with the CZTS−PtCo electrode was even smaller than that of CZTS−Pt, indicating a lower interface and thus charge transfer resistance from the material surface to the solution. 26 Jimmy. 15 Thus, more photogenerated charge carriers have the chance to participate in the hydrogen generation, leading to an improvement of the photocatalytic activity.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Furthermore, the radius of the semicircle obtained with the CZTS−PtCo electrode was even smaller than that of CZTS−Pt, indicating a lower interface and thus charge transfer resistance from the material surface to the solution. 26 Jimmy. 15 Thus, more photogenerated charge carriers have the chance to participate in the hydrogen generation, leading to an improvement of the photocatalytic activity.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The enhancement in the H 2 evolution in presence of graphene in TiO 2 could be due to excellent electron accepting and transferring capability, and the capacity to restrain the recombination of the photo-excited electrons and holes effectively. It has been reported that the two-dimensional π-conjugation structure of graphene sheets facilitates the transfer of photo-induced electrons and can act as an excellent electron acceptor [57,58]. A further increase in graphene content leads to a reduction of the photo-catalytic activity.…”
Section: Photo-catalytic Hydrogen Evolution From Plasmonic Active Phomentioning
confidence: 99%
“…[23][24][25][26] Photocarbocatalysis refers to the use of metal-free carbonaceous materials as photocatalysts and is aimed at replacing costly and critical metals using biomass as sustainable from renewable resources. Since the discovery of fullerenes, a large family of carbon nanoforms with remarkable photochemical properties has become increasingly available.…”
Section: Graphene Oxide In Photobiocatalysismentioning
confidence: 99%